Dialogic Approach to Teaching and Learning Environmental Management Accounting (EMA) in Tertiary Education - Raja-Adzrin R-A; Othman R; Othman N; Mohd-Tahir HHB; Amiruddin-Othman AM (Taylor and Francis Group, 2023)
This study focuses on an environmental management accounting (EMA) course and explores how a pedagogical project, incorporating dialogic environmental and sustainability elements, transforms students' perspectives and educational experiences. The findings support the shift towards a dialogic approach to enhance the educational experiences of tertiary accounting students, encouraging them to think creatively and critically and to aspire to become engaged citizens. Students' experiences with the dialogic approach were generally positive, with noticeable development of soft skills. They also expressed their aspirations as to what the future of accounting education should look like, including the structure, content, and delivery. However, both educators and some students reported a loss of control compared to the previously favoured monologic approach to teaching and learning. Lessons learned from this study highlight the potential of pedagogical interventions to improve teaching and learning outcomes, fostering a cycle of mutual learning that generates actions based on dialogical encounters.
Keywords: Accounting Education; Environmental Management Accounting (EMA); Pedagogic; Students; Tertiary